Evaluating the impact of housing interior design on elderly independence and activity: a thematic review - Mnea, Aysha; Zairul, Mohd (Multidisciplinary Digital Publishing Institute, 2023)
Concerns about a rapidly increasing elderly population mostly relate to the need for adequate housing and welfare for the aged. The poor design of housing for the elderly has led to the charge that the needs of aging people have not been adequately anticipated. There is little focus on design features that facilitate aging in place, hence improving the quality of life for the elderly, for example. This study examines the impact of interior housing design on the lives of the elderly, through a review of research on the subject and an evaluation of current design trends. Using a keyword search, 51 empirical studies from 2013 to 2022 that focus on housing for the elderly were identified and analyzed in terms of architectural features, home environment, and energy efficiency. The review found minimal connections have been made between interior design efforts and the actual housing needs of the elderly. This thematic review provides a summary of this literature for use by researchers and designers and recommends future studies for the use of inclusive designs in housing interiors in order to better meet the needs of elderly individuals.